Vascular disruption birth defects are not associated to chromosomal alterations (2015)
It is estimated that 2 to 35 of newborns present a congenital malformation. Some publications suggest that vascular disruption birth defects are not associated with chromosomal alterations detected by conventional karyotype. Objective: to determine the frequency of chromosomal alterations detected by high resolution G banded karyotype in patients with vascular disruption birth defects in a Colombian population (South America). Material and method: transversal study. Population: a sample of patients identified by an epidemiological surveillance system of congenital malformations in a reference hospital in Cali, Colombia. Results: 41 cases of vascular disruption birth defects were identified during a 36 month period; in a descending order those were: transverse reduction defects, hydranencephaly and gastroschisis. Two expert cytogenetists performed independent evaluation of the genetic material of the patients, and no chromosomal alterations detectable by G banded karyotype were identified. Conclusions: It is recommended that genetic counseling in cases of defects by vascular disruption is carried out taking into account the empirical recurrence risks reported for each one the types of defects by vascular disruption and the use of karyotype should be limited to cases with other malformations or chromosomal abnormality suspected by phenotype.